Pengembangan Media Pembelajaran Berbasis Flipbook Pada Materi Sistem Persamaan Linear Dua Variabel Dikelas VIII SMP - Widyasari, Intan; Zetriuslita, Zetriuslita; Istikomah, Endang; Herlina, Sari (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2021)
Technological progress is very rapid, especially in the field of education, so teachers and students need to use technology in learning. ICT-based learning media is one of the uses of technology in education with the hope of improving the quality of learning. This study aims to determine the process and produce a product in the form of-based learning media flipbook on the material of a two-variable linear equation system in class VIII SMP. This research is a development research using the ADDIE development model. The data collection technique used is a non-test technique with a data collection instrument in the form of a validation sheet filled out by the validator. Data analysis used quantitative descriptive data analysis. Overall, the feasibility assessment of-based mathematics learning media flipbook on two-variable linear equation system material obtained an average of 85.70%, so-based learning media flipbook on two-variable linear equation system material in class VIII SMP is interpreted as very valid for use.Keywords: Learning Media, Flipbook, Material of Two Variable Linear Equation Systems, Validity